Frontiers in Clinical Drug Research - Anti Infectives - Atta-ur-Rahman (Frontiers in Clinical Drug Research - Anti Infectives Ser., 2019)
Frontiers in Clinical Drug Research - Anti infectives is a book series that brings updated reviews to readers interested in learning about advances in the development of pharmaceutical agents for the treatment of infectious diseases. The scope of the book series covers a range of topics including the chemistry, pharmacology, molecular biology and biochemistry of natural and synthetic drugs employed in the treatment of infectious diseases. Reviews in this series also include research on multi drug resistance and pre-clinical / clinical findings on novel antibiotics, vaccines, antifungal agents.